2020
DOI: 10.1007/s00158-020-02532-4
|View full text |Cite
|
Sign up to set email alerts
|

Shape preserving design of thermo-elastic structures considering geometrical nonlinearity

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…To deal with this issue, the continuation strategy was proposed and found to be effective. 17,31,56,57 In this work, the continuation scheme is applied to the penalty factors: Another advantage of the continuation strategy lies in that the structure can be prevented, to a certain extent, from undergoing unreasonably high temperature. For example, consider the case of uniformly initializing all design variables to the upper bound of the volume constraint in TO.…”
Section: Continuation Strategy Of Penalty Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…To deal with this issue, the continuation strategy was proposed and found to be effective. 17,31,56,57 In this work, the continuation scheme is applied to the penalty factors: Another advantage of the continuation strategy lies in that the structure can be prevented, to a certain extent, from undergoing unreasonably high temperature. For example, consider the case of uniformly initializing all design variables to the upper bound of the volume constraint in TO.…”
Section: Continuation Strategy Of Penalty Factorsmentioning
confidence: 99%
“…Unless otherwise stated, temperature‐dependent thermal conductivity is interpolated using the RAMP scheme in this work: κi()Tigoodbreak=truexi1+Sκ()1goodbreak−xtrue‾iκfalse(0false)()Ti,$$ {\kappa}_i\left({T}_i\right)=\frac{{\overline{x}}_i}{1+{S}_{\upkappa}\left(1-{\overline{x}}_i\right)}{\kappa}^{(0)}\left({T}_i\right), $$ where S κ is the penalty factor for thermal conductivity. The coefficient of thermal expansion α i ( Ti ) is not interpolated since it does not change with xtrue‾i$$ {\overline{x}}_i $$ 31 …”
Section: Numerical Implementationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiphysics problems in optimisation are usually deemed to address thermal and mechanics conditions [521]. Recently, Cheng et al employed the Lattice Structure Topology Optimisation (LSTO) to design a cooling channel system [522] and Perumal et al found a technique to mitigate thermal accumulations by optimising lattice structures locally where such concentrations are more prone due to the metal AM process with a powder-bed fusion [523].…”
Section: Industrial Design Mechanical Engineering and Multiphysics mentioning
confidence: 99%